Short-Term Ability of Concrete Containing Palm Oil Fuel Ash Exposed to Sodium Sulphate - Ismail, M. H.; Deraman, R.; Majid, M. A.; Zainal Abidin, S. N. (International Journal of Integrated Engineering, 2022)
Uncontrolled palm oil waste disposal can lead to an environmental problem, and recycling the waste can assist in reducing the disposal problem. On another side, concrete exposed to sulphate normally will lose its strength after some time. Replacing cement with palm oil fuel ash (POFA) can lower the disposal issue and help reduce the concrete from strength losses. The main objective of this study is to investigate the short-term effects on the strength of concrete containing POFA exposed to sulphate solution. The POFA was prepared by drying in an oven for 24 hours at 105°C and sieved passing through a 300 ?m sieve. Then, the POFA had been refined using ball mills for two hours. The percentage of POFA as cement replacement used in this study is 10%, 20% and 30% by volume of cement. Two types of specimens were prepared, i.e., cube specimen (100 mm × 100 mm × 100 mm) and prism specimen (500 mm × 100 mm × 100 mm) that fully immersed in water and 3.5% sulphate solutions. Density test, water absorption test, compression strength test and flexural strength test were conducted after 7 and 28 days of the exposure period. A total of 144 specimens was subjected to these tests. The experiments show that concrete with 10% replacement of POFA had a higher slump value, while the density test showed that the 10% POFA mixture had a lower density than the other specimens. Furthermore, the water absorption test showed that more POFA in concrete contributes to higher water absorption when exposed to sulphate solution compared to water. In conclusion, the compressive strength and flexural strength test recorded replacement of 10% POFA is the highest strength of concrete containing POFA exposed to sulphate solution and water.